2019
DOI: 10.1530/joe-18-0203
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93 mediates cabergoline resistance by targeting ATG7 in prolactinoma

Abstract: To date, the management of dopamine agonist (DA)-resistant prolactinomas remains a major clinical problem. Previously, we determined that miRNA-93 expression increases in DA-resistant prolactinomas; however, the role of miRNA-93 in the DA resistance remains largely unexplored. Hence, this study aimed to investigate the susceptibility of tumor cells to cabergoline (CAB) and the autophagy changes in MMQ and GH3 cells after miRNA-93 overexpression or inhibition. We used bioinformatics to identify the potential ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…ATG genes are also involved in mediating resistance to chemotherapies, and these can be the potential targets for future treatment options. One known mechanism involves ATG‐7 gene, responsible for cabergoline resistance in prolactinomas and it gets mediated by miR‐93, which downregulates autophagy by targeting ATG‐7 140 . ATG7 overexpression is also involved in bladder cancer growth and tumorigenesis via FOXO1/p27 141 .…”
Section: Regulatory Factors With Mechanismsmentioning
confidence: 99%
“…ATG genes are also involved in mediating resistance to chemotherapies, and these can be the potential targets for future treatment options. One known mechanism involves ATG‐7 gene, responsible for cabergoline resistance in prolactinomas and it gets mediated by miR‐93, which downregulates autophagy by targeting ATG‐7 140 . ATG7 overexpression is also involved in bladder cancer growth and tumorigenesis via FOXO1/p27 141 .…”
Section: Regulatory Factors With Mechanismsmentioning
confidence: 99%
“…Recent evidence has revealed that several miRNAs are involved, among other functions, in regulating drug resistance in multiple tumors, including pituitary tumors (95)(96)(97)(98)(99).…”
Section: The Role Of B-arrestinsmentioning
confidence: 99%
“…miR-93, miR-17, miR-22, miR-126, miR-142-3p, miR-144, miR-486-5p, miR-451 and miR-92a were up-regulated while miR-30a, miR-382, miR-136 have been found down-regulated in BRC-resistant prolactinomas compared to BRC-sensitive prolactinomas ( 97 ). Interestingly, the knockdown of endogenous miR-93-5p by the miRNA inhibitor antagomir transfection in MMQ cells has been shown to significantly increase the sensitivity to BRC and CAB treatment inducing cell proliferation inhibition, whereas overexpression of miR-93-5p with the miRNA mimic agomir transfection blunted the anti-secretive effect of BRC on PRL release ( 95 ) and suppressed the cytotoxic effect of CAB in MMQ and GH3 cells ( 97 , 99 ). The DAs resistance induced by the overexpression of miR-93-5p in MMQ and GH3 cell lines involves the down-regulation of the protein p21, a key member of cyclin kinase inhibitors known to be implicated in the inhibition of cell-cycle progression, as demonstrated in MMQ cell line ( 97 ), and the down-regulation of the protein Autophagy Related 7 (ATG7), an essential regulator of autophagy, decreasing the autophagic cell death induced by CAB in MMQ and GH3 cell lines and rat pituitary tumors ( 99 ).…”
Section: Drs Expression In Pituitary Tumors: Mechanisms Of Resistancementioning
confidence: 99%
“…Wu et al [ 51 ] studied the involvement of miR-93 in resistant prolactinomas to dopamine agonists (DAs), such as cabergoline (CAB). They found that, in MMQ and GH3 cells, this miRNA was able to target autophagy-related gene 7 (ATG7) protein, leading to cell autophagy inhibition and CAB resistance, while the downregulation of miR-93 had the opposite effects, with subsequent increase in the apoptosis process.…”
Section: Mirnas In Secreting Pasmentioning
confidence: 99%